Geometric morphometrics shows differences and similarities in skull shape between the red and giant pandas. - Serrano Alarcón, Francisco José; Palmqvist-Barrena, Carlos Paul; Figueirido-Castillo, Francisco Borja (Wiley, 2011)
A morphometric analysis of the skull of the red or lesser panda, Aiulurus fulgens (Ailuridae), and the giant panda, Ailuropoda melanoleuca (Ursidae), was performed for evaluating the importance of natural selection and phylogenetic constraints in shaping the convergent morphological adaptations of these peculiar carnivores for feeding on bamboo. Principal components and discriminant analyses of landmark data was used in a comparative study across the families Procyonidae, Ursidae and Ailuridae. Skull morphospaces show that major patterns of morphological variation among these arctoid carnivorans correlate with differences in their feeding behavior. More specifically, this study has shown an extreme convergence in skull shape between the two bamboo specialists. Following the most recent molecular and morphological phylogenies, as well as the poor evidence from the fossil record, it seems highly improbable that homology could explain the shared morphology of the giant and red pandas, which lineages diverged ~40 million years ago. On the contrary, most phylogenetic and paleontological data suggest that convergent or parallel evolution (homoplasy) would be the evolutionary process shaping the common morphological traits of these unusual carnivorans. Therefore, the overall resemblance in skull shape between the giant and red pandas was probably driven by extrinsic factors (natural selection and adaptation for feeding on bamboo) as well as by intrinsic ones (the shared developmental pathway of the carnivoran skull, which posed some biomechanical constraints on the direction of the evolution of pandas).
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/21732
Keywords: Pandas rojos; Pandas gigantes; Craneometría; Ailuropoda melanoleuca; Aiulurus fulgens; Biomechanical constraints; Convergent evolution; Landmark-based morphometrics; Skull morphology